The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15361/2175-0106.2018v34n3p105-114
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhimurium Vaccine to Control a Brazilian Salmonella Heidelberg Strain in Broiler Chickens

Abstract: Foodborne Salmonella infections in humans, which results from the consumption of contaminated poultry meat and eggs, are a major public health concern. Vaccination of animals against Salmonella is one strategy to prevent these infections and reduce the risks to public health. Live attenuated Salmonella enterica vaccines can confer protection against salmonellosis by inducing both cell-mediated and mucosal immune responses. This study assessed a live, attenuated Salmonella enterica Typhimurium (ST) vaccine in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This may be due to the age difference between broilers and layers at the time of vaccination. The commercial vaccine failed to induce any pro- or anti-inflammatory cytokine production associated with poor T-cell responses in broilers [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the age difference between broilers and layers at the time of vaccination. The commercial vaccine failed to induce any pro- or anti-inflammatory cytokine production associated with poor T-cell responses in broilers [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Berghaus et al [ 74 ] reported that the use of a killed Salmonella vaccine reduced the incidence of Salmonella infection in broiler chicken flocks by more than 60%. Moreover, several previous studies recorded that the use of the Salmonella vaccine reduced the occurrence of Salmonella infections in poultry [ 33 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: A Review Of Current Research Studies On the Efficacy Of Bact...mentioning
confidence: 99%
“…Typhimurium ( Kogut et al, 2012) and S. Enteritidis (El-Ghany et al, 2012). Two studies found that a commercially available live-attenuated S. Typhimurium vaccine can also protect against S. Heidelberg (Hayashi, Tujimoto-Silva, et al, 2018;Muniz et al, 2017), and a live-recombinant S. Enteritidis vaccine was also seen to protect against S. Heidelberg ( Yang et al, 2017). In two live vaccine studies, there was no protection against heterologous challenge (Penha et al, 2010;Wolfenden et al, 2010).…”
Section: Salmonella Immunizationmentioning
confidence: 99%
“…Salmonella 4 (Berghaus et al, 2011;El-Ghany et al, 2012;Kogut et al, 2012;Pavic et al, 2010) 0 8 (De Cort et al, 2013;De Cort et al, 2015;De Cort et al, 2014;Hayashi, Tujimoto-Silva, et al, 2018;Imre et al, 2015;Muniz et al, 2017;Penha et al, 2010;Rubinelli et al, 2015) 2 (Wolfenden et al, 2010;Yang et al, 2017) 1 (Chalghoumi et al, 2009) 1 (Dorea et Layton et al, 2011;Nothaft et al, 2017) 1 (Hermans et al, 2014) 0 ceca to below the detection limit (Annamalai et al, 2013;Layton et al, 2011), while the remainder saw reductions of 0.64-3 log 10 CFU/g cecal contents (Hodgins et al, 2015;Kobierecka et al, 2016;Neal-McKinney et al, 2014;Singh et al, 2019;Taha-Abdelaziz et al, 2018). Notably in one study, the combination of probiotics with a vaccine candidate led to an average ∼7 log 10 CFU/g reduction, with C. jejuni below detection levels in the majority of birds, significantly more effective than separate use of the vaccine or probiotics alone (2 log 10 CFU/g reduction and no change at all, respectively) (Nothaft et al, 2017).…”
Section: Live Recombinant Passive Combinationmentioning
confidence: 99%